Assessment of perfusion MRI-derived parameters in evaluating and predicting response to antiangiogenic therapy in patients with newly diagnosed glioblastoma - Essock-Burns, Emma (Oxford University Press, 2011)
The paradigm for treating patients with glioblastoma multiforme (GBM) is shifting from a purely cytotoxic approach to one that incorporates antiangiogenic agents. These are thought to normalize the tumor vasculature and have shown improved disease management in patients with recurrent disease. How this vascular remodeling evolves during the full course of therapy for patients with newly diagnosed GBM and how it relates to radiographic response and outcome remain unclear. In this study, we examined 35 patients who were newly diagnosed with GBM using dynamic susceptibility contrast (DSC) MRI in order to identify early predictors of radiographic response to antiangiogenic therapy and to evaluate changes in perfusion parameters that may be predictive of progression. After surgical resection, patients received enzastaurin and temozolomide, both concurrent with and adjuvant to radiotherapy. Perfusion parameters, peak height (PH) and percent recovery, were calculated from the dynamic curves to assess vascular density and leakage. Six-month radiographic responders showed a significant improvement in percent recovery between baseline and 2 months into therapy, whereas 6-month radiographic nonresponders showed significantly increased PH between baseline and 1 month. At 2 months into therapy, percent recovery was predictive of progression-free survival. Four months prior to progression, there was a significant increase in the standard deviation of percent recovery within the tumor region. DSC perfusion imaging provides valuable information about vascular remodeling during antiangiogenic therapy, which may aid clinicians in identifying patients who will respond at the pretherapy scan and as an early indicator of response to antiangiogenic therapy.